(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Analyzing theoretical perspectives on management activities in higher educational institutions is a complex and multifaceted task, which requires a deep understanding of different approaches and practices used in different countries. Based on the experience of foreign countries such as the USA, Great Britain, Australia, Germany, and Canada, we can identify and offer solutions to the main problems of increasing the effectiveness of management in higher education is the diversity of practices across countries. Each country has its own system of higher education governance, which makes it difficult to make direct comparisons and identify universal best practices. To address this issue, researchers and policymakers can use a comparative approach, examining the strengths and weaknesses of different systems to inform their practice. Another issue is the evolving nature of higher education institutions and the increasing demands placed on governing boards. With the rise of digital technology, globalization and changing student demographics, institutions must adapt their management strategies to remain competitive and relevant. [4]